An Innovative Breast-Conserving Oncoplastic Technique for Treating Small to Medium Volume Breasts With a Tumor in the Lower Quadrant: The Folding Flap Technique - Shi, Wenjie; Wang, Maoli; Torres-de la Roche, Luz Angela; Shi, Xuefeng; Gong, Zhenyu; Dong, Jie; Chen, Zihao; Zeng, Jiajia; Jiang, Yicheng; Chen, Zhitong; Wu, Kejin; Zhuo, Rui; et al. (Frontiers in Oncology, 2022)
Abstract Background: Here, we describe an innovative oncoplastic technique for small to medium volume breasts with a tumor in the lower quadrant and this technique could provide sufficient tissue to avoid visible defects after tumor removal and help reshape the natural shape of the breast. Methods: A detailed procedure for the folding flap technique is described step by step. Then, the results of a retrospective analysis of patients treated using this technique, including complications and disease recurrence rate, between January 2017 and November 2021 are reported. Aesthetic outcomes were evaluated on a 5-point scale proposed by the Paris Breast Center. Results: A total of 52 patients underwent surgery with the folding flap technique, The average operation time was 98.4 min (range, 75–120 min), and the mean bleeding volume was 56.5 mL (range, 20–100 mL). A margin-positive result was confirmed in 1 patient who underwent re-excision. Short-term postoperative complications were observed in 7 patients, including 4 with fat liquefaction, 2 with seroma, and 1 with skin redness and swelling. No flap necrosis was observed. The median follow-up time was 28.6 months (range, 9–58 months), and 2 patients experienced local recurrence. The mean aesthetic score was 4.7 points, with 36 patients scoring 5 points and 26 patients scoring 4 points, respectively. Conclusions: The folding flap technique, as an innovative and favorable oncoplastic technique for treating small- to medium-volume breasts with a tumor in the lower quadrant, could retain sufficient tissue to fill the residual cavity after the operation while improving the aesthetic outcome of the breast.